2016
DOI: 10.1186/s13039-016-0261-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel microduplication of CHL1 gene in a patient with autism spectrum disorder: a case report and a brief literature review

Abstract: BackgroundThe cell adhesion molecule L1-like (CHL1 or CALL) gene is located on chromosome 3p26.3, and it is highly expressed in the central and peripheral nervous systems. The protein encoded by this gene is a member of the L1 family of neural cell adhesion molecules, and it plays a role in nervous system development and synaptic plasticity. Moreover, studies of mice have revealed that CHL1 is a prime candidate gene for a dosage-sensitive autosomal form of mental retardation. To date, four patients with a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Furthermore, 3p26 deletion disrupted a more distal gene: CHL1 that plays a crucial role in development of the cortex by regulating neuronal differentiation and axon guidance [27]. Previous studies suggested CHL1 as a dosage-sensitive gene with a main role in intellectual disabilities [28].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 3p26 deletion disrupted a more distal gene: CHL1 that plays a crucial role in development of the cortex by regulating neuronal differentiation and axon guidance [27]. Previous studies suggested CHL1 as a dosage-sensitive gene with a main role in intellectual disabilities [28].…”
Section: Resultsmentioning
confidence: 99%
“… TM4-3 3p26.3 159 kb gain CHL1 - CHL1 encodes a member of the L1 family of neural cell adhesion molecules, which plays a role in nervous system development and synaptic plasticity 85 , 86 . - Loss and gain of the CHL1 gene have been identified in patients with autism and ID 50 , 51 . AR12-3 18q22.3 217 kb gain ZNF407 - ZNF407 encodes a zinc finger protein which may be involved in transcriptional regulation.…”
Section: Resultsmentioning
confidence: 99%
“…In the five de novo CNVs, one was a large deletion associated with the known 9q21.13 microdeletion syndrome, while the other four were duplications ranging from 127–220 kb in size. These duplications contained recently identified ASD-associated genes, DPP10 49 and CHL1 50 , 51 , and two genes that are highly expressed in the brain, but have not yet been linked to ASD, namely carnosine dipeptidase 1 ( CNDP1 ) and serine incorporator 2 ( SERINC2 ). Duplications of neither SERINC2 nor CNDP1 have been reported in the Thai CNV database 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 3p26 deletion disrupted a more distal gene: CHL1 that plays a crucial role in the development of the cortex by regulating neuronal differentiation and axon guidance [27]. Previous studies suggested CHL1 as a dosagesensitive gene with a major role in intellectual disabilities [28]. Interestingly, Frints hypothesized that a reduction equal to 50% of chl1 in the developing brain marked cognitive deficit [29].…”
Section: Discussionmentioning
confidence: 99%